Ilusi Kohesivitas Tim Bayangan Kemendikbudristek Pendekatan Groupthink Teori - Tumpal Daniel S (STIT Muslim Asia Afrika, 2022)
Qualitative research with a groupthink theory approach describes the reality of the policies of the Minister of Education, Culture, Research and Technology, Nadiem Makarim by appointing 400 “Shadow Teams” within his ministry. Bureaucratic procedural issues to policy products produced by “the Shadow Team have raised pros and cons in the public sphere. Primary data was extracted from the organizational nomenclature of the Ministry of Education and Culture, official statements of the Minister of Education and responses from Indonesian education stakeholders. Secondary data were obtained from the literature and related previous studies. The data were analyzed using Irving L Janis' groupthink theory, with an emphasis on the assumption of structural dominance and the illusion of cohesiveness among education stakeholders. The results showed that the